EXPAREL® (Long-Acting Liposomal Bupivacaine) Use for Popliteal Nerve Block in Postoperative Pain Control after Ankle Fracture Fixation - Patrick Discepola; Mohamed Bouhara; Minho Kwon; Bilal A. Siddiqui; Trevor A. Whitwell; Swetha Y. Sanghvi; Keith D. Cook; Ross E. Moore; Anna Korban; Jean D. Eloy (Pain Research and Management)
EXPAREL® has been used successfully to prolong postoperative pain control when applied as a wound infiltrate. EXPAREL® has not yet been approved for use in regional anesthesia to prolong postoperative pain control. We conducted a clinical case series of 4 patients using EXPAREL® for sciatic blocks via the popliteal fossa approach. Our results suggested that there is a large degree of variability in response to the medication. These inconsistent results and the possibility of bimodal kinetics creating analgesic gaps as seen in two of our patients indicate that more studies with larger sample size are needed to better characterize these phenomena and determine if more consistent results can be obtained in a future clinical trial.